Inherent potential of steelmaking to contribute to decarbonisation targets via industrial carbon capture and storage - Tian, Sicong; Jiang, Jianguo; Zhang, Zuotai; Manovic, Vasilije (Cranfield University, 2018)
Accounting for ~8% of annual global CO2 emissions, the iron and steel industry is expected to undertake the largest contribution to industrial decarbonisation. Despite the launch of several national and regional programmes for low-carbon steelmaking, the techno-economically feasible options are still lacking. Here, based on the carbon capture and storage (CCS) strategy, we propose a new decarbonisation concept which exploits the inherent potential of the iron and steel industry through calcium-looping lime production. We find that this concept allows steel mills to reach the 2050 decarbonisation target by 2030. Moreover, only this concept is revealed to exhibit a CO2 avoidance cost (12.5–15.8 €2010/t) lower than the projected CO2 trading price in 2020, whilst the other considered options are not expected to be economically feasible until 2030. We conclude that the proposed concept is the best available option for decarbonisation of this industrial sector in the mid- to long-term.